Applying the Concepts of M. Heidegger’s Philosophy for the Quest Reflection of God in XXth Century Protestant Theology - Briedis, Mindaugas (Problemos, 2007)
The article explores fundamental shifts in protestant theology during the first half of the 20th century and reflects their philosophical premises deduced from philosophical hermeneutics, primarily from the philosophy of M. Heidegger. On the one hand, the methods and the content of philosophical hermeneutics respond to the issues posed by contemporary philosophy of religion. On the other hand, theology as a rational, critical discipline cannot ignore the polemic horizons explored by philosophical hermeneutics. One of such underlying polemic questions is the problem of theological language, which was “forgotten” simultaneously with the rise and development of the tradition of metaphysical theism. The thesis of the article, stating that there is no principle disagreement between philosophical hermeneutics and the objectives of contemporary theology, is based on a careful analysis of prominent protestant theologians (K. Barth, R. Bultmann, P. Tillich) of the period and supported by the interpretations of authoritative critics (J. Macquarrie, K. Lowith). While answering the question how, in the face of the new ontology (hermeneutics of finitude), theology is possible, the answer comes in the form of “the language of being” which rehabilitates traditional symbols retaining their transforming power and existential conceptuality. After stating that Dasein analytics presented by M. Heidegger provides new impulses for the theological discourse, it is also noted that we must take a closer look at the so-called contemporary” theology and explore the critical revision of this very modern “theologization” of Heidegger, accomplished by postmodern theologians (J. L. Marion).
Keywords: philosophical theology, protestantism, Heidegger, Being, Dasein